Implementation of Problem Based Learning Model Based on Monera Kingdom to Increase the Learning Outcomes and Critical Thinking Skills - Mukti Hastuti Nurinayah; Aminuddin P. Putra (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Permendikbud No. 65 of the standard curriculum in the learning process 2013 highly recommended approach is to use learning approaches that produce work. Based on these models are suitable is Problem Based Learning models.  Problem Based Learning models is designed to help students develop thinking skills, problem-solving skills, and intellectual skills. This research aims to improve learning outcomes and critical thinking skills studentsSMA 5 Banjaramasin to the application of Problem Based Learning models. This research is a classroom action research conducted in two cycles, each cycle of 2 meetings. The subjects were students of class X MIA 4 SMA Negeri 5 Banjarmasin. Cognitive learning outcomes of students has increased of the first cycle of 36.2% and cycle II of 90.7%, from the data obtained indicate achievement of classical completeness is set at ≥ 85%. Results of the assessment process is fair in every cycle. LKS assessment results classified as good in every cycle, the first cycle of 76.57% and 88.69% second cycle. Assessment of products / works has increased from 73.19% the first cycle and 83.59% second cycle. Affective student assessment results quite well on the assessment of character behavior and social skills in every cycle. Assessment of critical thinking skills of students has increased from 73.55% the first cycle and cycle II 82.11%, from the data obtained shows that the achievement of success indicators research students' critical thinking skills quite well. Students' response to the application of Problem Based Learning models showed high positive answer is 55.41% of students agreed. Under these conditions, the application of the model Pembelajaran Berdasarkan Problems can improve learning outcomes and the critical thinking skills of students on the Monera Kingdom Concept.Keywords: Monera Kingdom Concept, Problem Based Learning Model, the Learning Outcomes and Critical Thinking Skills